Characterization of the Lipid Fraction of Wild Sea Urchin from the Sardinian Sea (Western Mediterranean). Issue 2 (21st January 2014) - Angioni, Alberto; Addis, Pierantonio
Abstract The fatty acid (FA) composition of Spatangus purpureus, Echinus melo, Sphaerechinus granularis, and Paracentrotus lividus, sea urchins, has been studied. Sea urchins were collected at different depth along Sardinia coast in the Mediterranean sea, and their gonad was measured, separated, and analyzed for FA composition by gas chromatography‐mass spectrometry. A total of 53 FAs were detected, 16 saturated (SFA), 10 monounsaturated (MUFA), 9 polyunsaturated (PUFA), and 13 highly unsaturated (HUFA). Moreover, 5 furan FAs (FFAs) were revealed for the first time in sea urchin. The HUFA and PUFA classes were the most represented accounting for almost 80% of total FAs. Among these compounds, C20:4 n6 (19.64, 20.52, 23.37, and 8.48 mg/g, respectively) and C22:6 n3 (19.68, 20.05, 3.83, and 1.78 mg/g, respectively) were the most abundant. The results of principal component analysis indicated that the sea urchin samples could be clearly discriminated with respect to their FAs composition.